Pre-Service English Teachers’ Pedagogical Competence in Teaching English: A Case of Teaching Internship Program (TIP) - M. Ali Ghufron; Ahmad Taufiq; Muhammad Riskiyanto (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2022)
Pre-service English teachers (here: PETs) play a critical role in the development of students’ academic knowledge, technical skills, social values, and individual personalities, as well as their ability to digest teaching materials properly. Considering what is known as the pedagogical competence of pre-service English teachers is an important part of this process. This study aimed at evaluating the pre-service English teachers’ pedagogical competence in the classroom while instructing pupils in the English language. This study employed a qualitative research approach, especially a case study method with five Indonesian pre-service English teachers who participated in a teaching internship program (TIP) to collect information. The researchers used a range of approaches to acquire information from the perspectives of the student-teachers. These methods included questionnaires, observations, and observation notes. During the data analysis phase, the researchers used data reduction, data visualization, conclusion writing, and verification to help them make sense of their findings. In addition, the triangulation procedure was used to examine and validate the information gathered from the participants throughout the research phase of the investigation. According to the results of this research, pre-service English teachers' pedagogical competence was good, with an average score of 3.33 out of 5 on the pedagogical competence score (67 percent). Pre-service English teachers will benefit from reflection-based instruction and extended teaching practice under the supervision of experienced instructors in English Language Teaching (ELT) practices.